Preliminary design and analysis of a photovoltaic-powered direct air capture system for a residential building - Al Assaf, AH; Alrebei, OF; Le Page, LM; El-Sabek, L; Obeidat, B; Kaouri, K; Abufares, H; Amhamed, AI (MDPI, 2023)
To promote the adoption of Direct Air Capture (DAC) systems, this paper proposes and tests a photovoltaic-powered DAC system in a generic residential building located in Qatar. The proposed DAC system can efficiently reduce CO2 concentration in a living space, thus providing an incentive to individuals to adopt it. The ventilation performance of the building is determined using Computational Fluid Dynamics (CFD) simulations, undertaken with ANSYS-CFD. The CFD model was validated using microclimate-air quality dataloggers. The simulated velocity was 1.4 m/s and the measured velocity was 1.35 m/s, which corresponds to a 3.5% error. The system decarbonizes air supplied to the building by natural ventilation or ventilation according to the ASHRAE standards. Furthermore, the performance of the photovoltaic system is analyzed using the ENERGYPLUS package of the Design Builder software. We assume that 75% of CO2 is captured. In addition, a preliminary characterization of the overall system’s performance is determined. It is determined that the amount of CO2 captured by the system is 0.112 tones/year per square meter of solar panel area. A solar panel area of 19 m2 is required to decarbonize the building with natural ventilation, and 27 m2 is required in the case of ventilation according to the ASHRAE standard.